Shape induced sorting via rim-to-rim complementarity in the formation of pillar[5, 6]arene-based supramolecular organogels. Issue 19 (20th August 2019) - Kaizerman-Kane, Dana; Hadar, Maya; Granot, Eran; Patolsky, Fernando; Zafrani, Yossi; Cohen, Yoram
Abstract : The first two-component rim-to-rim pillar[6]arene-based supramolecular organogels were prepared. Shape complementarity was found to be an important determinant in the formation of such gels which also show shape-induced sorting in their formation. Abstract : Two-component supramolecular organogels based on per-carboxylato- and per-amino pillar[6]arenes (2 and4a–c ) were prepared for the first time, and found to display very different characteristics as compared to those displayed by the corresponding pillar[5]arene derivatives (1 and3a–c ). Pillar[6]arenes derivatives, in contrast to pillar[5]arene derivatives, do not form organogels in alcoholic solutions and the formed gels in chlorinated solvents are, generally, more fragile. We analyzed the gelation ability of all the pairs between1, 2, 3a–c and4a–c, several three-component mixtures in 1 : 1 : 1 and 2 : 1 : 1 ratios, as well as four-component mixtures in ∼10 : 1 CDCl3  : DMSOd6 solutions. The obtained results clearly show that shape complementarity is an important determinant of gel formation in these supramolecular pillar[ n ]arene-based organogels. We also found that shape directed molecular sorting occurs in the gelation process of these two-component supramolecular organogels.